Parents' Perceptions of Preschoolers' on the Use of Gadget : Measured by Digital Literacy and Socioeconomic Status - Muliani, Andi St.; Pranoto, Yuli Kurniawati Sugiyo; Formen, Ali (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
The use of gadgets is increasingly prevalent among preschool children, especially in today's digital era. The use of gadgets by preschool children often raises pros and cons among parents and educators, regarding its positive and negative impacts on child development. This type of research is